Long term players development in Rugby Union - Nakatake, R.; Yamamoto, T.; Sasaki, K.; Ueno, Y. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The structure in LTPD would be produced in some decisive momentum in the Union. JRFU will bid the 2019 Rugby World Cup and will be expected the responded result. Arround 2010, JRFU has launched the LTPD as one chart for challenging road towards 2019 Rugby World Cup. This study clarifies the practical concept and the concrete planning strategy. Results & Discussion For planning, the Union starts the analysis of SWOT (Strength, Weakness, opportunity, Threat) for positioning in the International Ranking. The characteristics suggest the priority for planning and the concrete tasks. In the world ranking system as very crowded tight schedule /calendar in years, the each football union would like to make a favorite match and it need tough negotiation. In the same time, the union needs to enhancement for young talented players` development and local coaches` development and the process should be educated along the consistent doctrine. For second tier union, some unique doctrine and strategy must be created for challenging towards the 1irst tier Unions. The strategy / tactics are based on the scientific, logical, and enterprise benchmarks. JRFU set the professional instructors like, "Coaching Director", "high Performance Director", "Resource Coaches" and "Science & Intelligence division", and cumulate the LTPD evidences. The football contains Technical, Physical strength, Psychological / Mental and Tactical factors and the condensed factors. Very humanistic and synthetic capital, we discuss the football perspective openly.